PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI UNIVERSITAS PGRI PALEMBANG - Kurniawan, Chandra (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
The purpose of this study was to determine the effect of motivation and leadership on employee performance in Universitas PGRI Palembang. The research method used was survey with quantitative explanative approach. The population in this research were the administrative staff of Universitas PGRI Palembang which consist of 388 people. The sampling technique used was Proportionate Stratified Random Sampling where sampling method taken from the population is done proportionally by taking into account the strata in the population. The number of samples taken was 10% of the total population of 39 respondents. Statistical analysis used for hypothetical action in this research was descriptive analysis and path analysis. The results of the analysis showed that (1) the better motivation of employee performance of Universitas PGRI Palembang, then the performance of employees will also be increased; (2) The better the leadership in Universitas PGRI Palembang, then the performance of employees will also be increased; and (3) the joint better of motivation and leadership on the performance of Universitas PGRI Palembang, then the performance of Universitas PGRI Palembang staff will also be increased.